Synthesis and Self‐Assembly Properties of New Surface‐Active 1‐Alkylimidazolium Ionic Liquids in Aqueous Media. Issue 3 (4th February 2019) - Adam, Claudia G.; Fortunato, Graciela G.
Abstract: New cationic surface‐active ionic liquids (SAIL) were synthesized using 1‐alkylimidazolium cations [CnHim] ( n = 8, 10, 12, 14, and 16) with trifluoroacetate ([CF3 CO2 ]) and methanesulfonate ([CH3 SO3 ]) anions as counterions. Their self‐aggregation behavior in water was investigated using electrical conductivity and fluorescence measurements. Based on the obtained results, the critical micellar concentration (CMC), the degree of counterion dissociation, α, the Gibbs free energy of micelle formation, Δ G mic 0, and the mean aggregation number ( N agg ) were determined. The analysis of these parameters indicates that these new SAIL exhibit certain improved properties with respect to traditional cationic surfactants. Furthermore, SAIL with [CF3 CO2 ] counterions exhibit lower CMC values than alkyltrimethylammonium bromide (Cn TAB)‐type surfactants and their dialkylimidazolium counterparts with the same alkyl chain length. It was demonstrated that, in the studied SAIL, the hydrophobic probe pyrene resides deeper inside the palisade layer of the micelle and the estimated E T (30) polarity values of micellar pseudophase confirm this result. The abovementioned outcomes demonstrate that the 1‐alkylimidazolium cation is suitable to promote aggregation when it is accompanied by the appropriate counterions. Consequently, this contribution becomes a valuable first step toward the potential application of these compounds as a new class of "designed cationic surfactants."